UPAYA GURU DALAM MENGATASI KESULITAN BELAJAR ANAK DI RA AL AMNANIYAH PARAS PANGKUR NGAWI PADA MASA PANDEMI COVID 19 - Prasetiyo, Eko; Munafiah, Khoirul (Early Stage, 2023)
The Covid-19 pandemic that has hit the world, including Indonesia, requires taking a stand in preventing wider transmission, including the education sector. This paper examines efforts to overcome learning difficulties during the pandemic at RA Al Amnaniyah Paras Pangkur Ngawi. The distance learning process (online) is a solution which in its implementation is not optimal as a whole. There are so many difficulties experienced by both the educators, parents and also the students themselves of course. From the educator side, it is clear that they have difficulty delivering learning materials, assessing every development and also trying to keep students enthusiastic about learning and of course being able to understand what is being conveyed even though learning is not delivered directly. Of course, this is a new challenge for educators, especially early childhood educators. From the parents' side, many parents complain about online learning. Especially the parents whose children are still young. They admit that they don't have enough tricks to make their young children learn properly. Because it is clearly different from children who are already elementary, junior high or even high school. So they find it difficult to accompany their children to study or in other words become a substitute for their teacher at school. From the side of the students themselves, it is clear that the characteristics of early childhood are love to play. So learning cannot be given just like that, learning must be given by playing. Can not be too forced let alone until they feel pressured. So it is certain that they will find it difficult if the learning is not given as it should be given to early childhood. From the results of the study, it is proven that distance learning due to the pandemic is very ineffective. Many students have difficulty in learning. Both difficulty reading, writing, counting and concentration. Based on the research, data were obtained from 24 children, 12 of whom had difficulty reading, 8 children had difficulty writing, 16 children had difficulty counting and 4 children had difficulty concentrating. Keywords: Learning Difficulties, teacher efforts, Covid-19 pandemic